The Legal Protection of Sustainable Agricultural Land: Why is It Urgent? - Ivan Fauzani Raharja; Hafrida Hafrida; Retno Kusniati; Sasmiar Sasmiar; Ahmad Ridha (Faculty of Law, Jambi University, 2021)
The phenomenon of rapid population growth and land conversion is what forms the background of this study. The Indonesian state does not only lose its agricultural land but also its farmers. This is the concern of the Government, including Local Governments, considering that agricultural land in its territory needs to be saved for food security and the needs of the next generations. Indonesia, including Jambi Province, will no longer have agricultural land and enough farmers in the future if this condition continues. Sungai Penuh of Jambi Province has been chosen as an object of study since this city is one of the main rice producers but suffering from agricultural land conversion. In realizing the goal, Legal policy is an option to implement because it binds not only the Local Government but also the community. That’s why it is important to protect agricultural land through a legal framework to ensure the availability of agricultural land. This article argues that the problem has to find ways by establishing local regulation to protect the sustainability of land and the prosperity of the farmers as well as by providing comprehensive incentive programs for those who conserve it.